2015
DOI: 10.1038/ejcn.2015.170
|View full text |Cite
|
Sign up to set email alerts
|

Fluid intake and hydration status in obese vs normal weight children

Abstract: Obese children were less hydrated than normal weight ones because, taking into account their z-BMI, they drank less. Future prospective studies are needed to explore possible causal relationships between hydration and obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 26 publications
2
31
2
Order By: Relevance
“…However, we could not find the difference in total sugar consumption between overweight and normal weight ADHD subjects. Recently, studies suggest that the hydration status not only help the performance of cognition in 9–12 year-old children but also help the alleviation of weight gain in overweight children [3233]. In this study, we could not find the difference in water consumption between overweight and normal weight subjects.…”
Section: Discussioncontrasting
confidence: 65%
“…However, we could not find the difference in total sugar consumption between overweight and normal weight ADHD subjects. Recently, studies suggest that the hydration status not only help the performance of cognition in 9–12 year-old children but also help the alleviation of weight gain in overweight children [3233]. In this study, we could not find the difference in water consumption between overweight and normal weight subjects.…”
Section: Discussioncontrasting
confidence: 65%
“…Previous studies on adults evaluated postprandial lipaemia after a higher amount of fats [18,19]. However, we decided to use a test meal, which respected the national RDI, with a fat intake of 35% of total energy [20] and closer to that reported in a previous study conducted in obese children leaving in the same geographical area [21]. This choice allowed exploring the response to PGR in condition closer to real life.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the elevated levels of U BPA had increased risks of paediatric obesity, whereas no effects of U BPA‐Cr on obesity were observed. These conflicting findings could be explained by the fact that hydration status and body compositions were different between children with obesity and those without . Indeed, a previous study showed that children with obesity consumed less water and subsequently were more likely to be dehydrated, suggesting elevated urinary osmolarity.…”
Section: Discussionmentioning
confidence: 99%